The Effect of Green Social Media Marketing on Purchase Decision: A Systematic Literature Review - Handoko, Wisnu; Roziki, Abda Ali; Ferdinand, Augusty Tae (Research Horizon, 2024)
The past few decades have witnessed a dramatic rise in consumer interest for environmental protection, pushing companies to adopt more sustainable practices. This shift is reflected in the explosion of green marketing, particularly on social media platforms. Social media serves as an important communication channel for today's environmentally conscious and socially active consumers, making it a prime target for companies promoting eco-friendly products and initiatives. While prior research has explored green marketing in general, the specific influence of green marketing on social media and its impact on consumer purchase decisions remain relatively under-investigated. This systematic literature review, conducted using PRISMA guidelines, analyses relevant academic journals published between 2019 and 2024. It examines how companies leverage social media using green marketing, and how these efforts influence consumer’s purchase decision journey. This in-depth analysis provided a descriptive breakdown of the included articles, categorizing them by author, publication year, journal, citations, and other relevant information. This systematic review offers valuable insights into current trends within the realm of green social media marketing. It not only highlights established research directions but also pinpoints areas where further investigation is crucial. This comprehensive literature review outlines current trends on the topic, identifies gaps in existing research, and proposes directions for future studies.